Development of Student Worksheet on Fluid Material by Integrating Guided Inquiry Model to Promote Students' Science Process Skills - Chintya Larayesa Satria; Asrizal Asrizal; Yurnetti Yurnetti; Hidayati Hidayati (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
The teaching materials used by schools experience a lack of quality teaching materials or are not available at all. The standard of teaching materials that do not meet student requirements causes them to be unable to accommodate various levels of student ability, including in training student skills. In the era of competency-based curriculum, teaching materials should be capable of supporting the enhancement of student skills. The focus of this problem is a cause of weak science process skills amongs students. This study purpose to produce a Guided Inquiry Student Worksheet (SWS) Model to Develop Science Process Skills in Fluid Material for Class XI / Phase F that is valid and practical. The research approach is Research and Development (R&D) using 4D. Research is limited to the practicality stage in small group tests. The instruments used are validation questionnaires and practicality questionnaires. The data source obtained from the validation results by 3 experts. The practicality data source obtained from teachers and students of class X SMAN 16 Padang. The data analysis technique to analyze the level of validity of Students Worksheet (SWS) uses a Likert scale with the Aiken's V formula and analyzes the practicality of Students Worksheet (SWS) using a statistical analysis formula. The validation results of the Guided Inquiry model students worksheet obtained a value of 0.87 in the very valid category. The teacher's practicality score of 99% places it in the very practical category, while the student’s score of 90% also falls within this category.